Possible Polarization Measurements in Elastic Scattering at the Gamma Factory Utilizing a 2D Sensitive Strip Detector as Dedicated Compton Polarimeter. Issue 3 (14th December 2021) - Middents, Wilko; Weber, Günter; Spillmann, Uwe; Krings, Thomas; Vockert, Marco; Volotka, Andrey; Surzhykov, Andrey; Stöhlker, Thomas
Abstract: For photon energies from several 10 keV up to a few MeV Compton polarimetry is an indispensable tool to gain insight into subtle details of fundamental atomic radiative processes. Within the SPARC collaboration several segmented semiconductor detectors are developed that are well suited for application as efficient Compton polarimeters. In this report, these recent developments are reviewed and it is discussed how Compton polarimetry can be employed at the upcoming Gamma Factory. Abstract : Compton polarimetry provides indispensable insights into fundamental radiative processes with photon energies from tens of keV to several MeV. Within the SPARC collaboration multiple segmented semiconductor detectors are developed as dedicated Compton polarimeters. Presented are recent developments, with a focus on polarization studies of elastic X‐ray scattering, and the possibility of a new access to Delbrück scattering utilizing Compton polarimetry.